Kasba (White Partridge): A Story of Hudson Bay - Ray, George R., 1869-1935 (Salt Lake City, UT : Project Gutenberg, 2016)
"KASBA (White Partridge): A Story of Hudson Bay" by George R. Ray is a novel written in the early 20th century. The narrative unfolds against the stark and beautiful backdrop of Hudson Bay, focusing on the life of Roy Thursby, an officer of the Hudson$1 (Bs Bay Company, and the complicated relationships between him, a young Chipewyan girl named Kasba, and other characters in their remote community. The themes of love, cultural identity, and conflict are apparent from the outset, as the story navigates the tensions between indigenous customs and colonial influences. At the start of the story, the reader is introduced to the harsh winter landscape of Hudson Bay through the experiences of Roy Thursby as he tends to his traps. While examining the icy wilderness, he encounters Kasba, a Chipewyan girl, who becomes the subject of unwanted attention from a character named Broom. The opening portion sets a tense scene with Broom's aggressive actions toward Kasba, prompting Roy's protective instincts. As Roy attempts to defend her, both characters grapple with their emotions and cultural positions, hinting at a deeper conflict that will unfold involving love, duty, and societal expectations as the narrative progresses. (This is an automatically generated summary.)s
Release date is 2016-09-30
E-text prepared by Mardi Desjardins and the online Distributed Proofreaders Canada team
Keywords: Hudson Bay -- Fiction